Entrepreneurial finance and new venture success ‐ the moderating role of government support. Issue 4 (23rd February 2020) - Anwar, Muhammad; Tajeddini, Kayhan; Ullah, Rizwan
Abstract: The high failure ratio in newly born ventures across the globe has been raised a challenging question. Numerous strategies have been introduced to enhance the survival of new ventures in the long run, but the results are fragmented. The research model examined the influence of entrepreneurial finance on new venture success. The model also considered a moderating role of government support while predicting ventures success. This area is under‐researched particularly in the context of Pakistan; therefore, this research may contribute to the existing body of knowledge to appraise the industry in Pakistan. Data were collected from 182 new ventures operating in an emerging economy in Pakistan and analyzed by SmartPLS. The results indicate that entrepreneurial finance and government support have a significant influence on new venture success. Moderation analysis demonstrates that government support strengthens the relationship between entrepreneurial finance and new venture success. The findings suggest implications for policymakers to initiate effective policies and programs for newly started ventures regarding financial and nonfinancial support; in this backdrop, the incubation services are important.